Beyond Tobacco: Bridging Gaps in Social History Records for Tobacco‐Free Nicotine Pouch Consumers - Taylor J. Stack; Morgan N. McCain; Ezer H. Benaim; Theresa A. Dickerson; Ibtisam Mohammad; Brent A. Senior; Adam J. Kimple; Christine DeMason (OTO Open)
Abstract Objective Nicotine‐containing products have historically been tobacco derivatives like cigarettes, cigars, and dip. Recently, tobacco‐free nicotine (TFN) products have been marketed as a healthy alternative. TFN pouches are small, discreet, flavored pouches containing nicotine designed to be placed between the gum and lip. This product does not fit a conventional tobacco category, leading to inaccurate reporting. This study aims to investigate discrepancies in physician documentation of TFN pouches. Methods A retrospective chart review was conducted on TFN users. Setting Single Health Care System. Methods Statistical analyses assessed TFN documentation concordance between social history templates and physician notes. Results There were 150 patients who used TFN and 841 patients who vaped. Concordance was higher for vape documentation than TFN pouch documentation (55.9%, 470/841 vs 25.3%, 38/150; P < .001). Of those who used TFN, 60% (90/150) were classified as “Smokeless Tobacco Users” in the social history; however, 35 were inaccurately classified as chew, and 17 did not specify TFN use. Only 38 specified TFN use; only 25% (38/150) of records demonstrated concordance. Conclusion Only 25% of records were concordant with physician notes, highlighting the need for a designated place for TFN use within social history templates. Nicotine use history is crucial in the setting of microvascular reconstruction and cosmetic surgeries. Thus, accurate reporting is crucial for future research on the long‐term effects of TFN. This study's findings underscore a deficit in current social history templates and the need to recognize TFN pouches as distinct entities.